ARTIFICIAL INTELLIGENCE APPLICATIONS AND THEIR IMPACT ON IMPROVING STRATEGIC COST MANAGEMENT TECHNIQUES - Nowfal Hussien Abdulaah; Ismael abbas manhel; Haider atta zabin (Scholar Express Journals, 2025)
The study aims to explore the role of artificial intelligence applications in improving strategic costing techniques. With competition and rapid development, companies seek to respond to changes in the business environment by relying on artificial intelligence applications to improve performance and enhance production processes. This is in addition to improving decision-making processes and generating alternatives to maintain market value, confront competitors, and improve their strategies, particularly in the field of cost accounting, which is one of the key and important factors determining success. A descriptive analytical approach was used, represented by a questionnaire distributed to a sample of specialists, including academics, producers, and businessmen. The study reached a set of conclusions, the most important of which is that there is a significant relationship between artificial intelligence applications and cost and administrative accounting, which contributes to enhancing the efficiency of production and operations within companies, as well as decision-making, accuracy, ease of access to information, and cost reduction.
Keywords: Artificial intelligence; cost management techniques; Expert systems